New species of Clavicornaltica Scherer (Coleoptera: Chrysomelidae) from continental Asia - Konstantinov, Alexander S.; Duckett, Catherine N. (Zootaxa, 2005)
Four new species of Clavicornaltica Scherer are described and illustrated, of which two are from China (C. dali new species and C. longsheng new species) and two are from Vietnam (C. tamdao new species and C. vietnamensis new species). The wing and metathorax are described and illustrated for the genus for the first time. A key to the newly described species is presented. Male genitalia of Clavicornaltica australis Konstantinov are illustrated for the first time.